Hubungan Pendidikan dan Paritas dengan Keikutsertaan Ibu Hamil dalam Kelas Yoga di Desa Kalipang Kabupaten Kediri - Elin Soya Nita; Lailaturrohmah Lailaturrohmah (Journal of Pharmaceutical and Health Research, 2023)
Pregnancy is a natural method experienced by women and is not included in the pathological category except in special conditions, because pregnancy will experience both anatomical, physiological and biochemical adaptations which increase according to gestational age. During pregnancy there will be changes in all body systems both physically and psychologically One method that can be used to help and relieve pregnant women in preparing for a healthy pregnancy and physiological delivery is exercise. One good exercise for pregnant women is yoga for pregnant women / prenatal yoga. This research is a type of analytic quantitative research using a cross-sectional approach with the independent variables being Education and parity and the dependent variable being the participation of pregnant women in yoga classes with analysis using the Chi Square test. Total sampling data analysis. From the research data, the results of statistical analysis showed that there was no relationship between education and parity with the participation of pregnant women in yoga classes in Kalipang Village, Kediri Regency in 2023 with a P value of 0.463.